Nursing actions and interactions in the recovery of patients with chronic renal failure: Integrative review (Research, Society and Development, 2021)
Objective: To analyze what has been published about the role of nurses in the recovery of patients with renal failure. Method: an integrative literature review carried out in a Latin American and Caribbean Health Sciences electronic database (LILACS), (BDENF) Nursing Database and (SciELO) Scientific Electronic Library Online, with a time frame of the last five years in Portuguese and English and had as exclusion criteria incomplete, repeated articles that did not fit the theme. Result and discussion: A sample of 7 studies was obtained, all published in nursing journals. Among the findings, the fundamental role of nurses in the process of adapting chronic renal patients to their new reality and understanding was evident. Conclusion: The present study allows us to know the demonstration of the performance of nurses who work by virtue of minimizing the worsening of the chronic renal failure disease and also their own knowledge of the care provided.